Analisis Multitemporal Topografi Pesisir Wonorejo Surabaya dan Pengaruhnya Terhadap Distribusi Sedimen Menggunakan Software ArcGIS 10.3 - Ulfah Nurjanah; Ety Parwati; Pingkan Mayestika; Retno Hartati (Jurnal Perikanan dan Kelautan, 2022)
Sediment is a collection of particles that come from weathering both soil and rock, biological and an anthropogenic process. Sediment flows from upstream to downstream areas. Topographic conditions are one of teh factors in sedimen distribution. The topography in the Wonorejo area tends to be low because it is located in a coastal area. The purpose of this study is to determine the effects of topographic changes in Wonorejo on the distribution of sediments in the area. The method used in this study is descriptive method by collecting data including primary data and secondary data. The primary data used are Landsat 7 and Landsat 8 satellite imagery, while the secondary data used is in the form of Surabaya village administration map data, Surabaya DEM data and Indonesian SHP data. Data processing was performed using ArcGIS 10.3 software. The results indicated that the topographic conditions of the region did not have a significant influence on the distribution of sediments in the Wonorejo area. The distribution of sediment in those area was more influenced by hydro-oceanographic factors such as currents, tides and waves. Other factors that influence are anthropogenic factors such as development and land conversion